Pathogens, prejudice, and politics: the role of the global health community in the European refugee crisis. Issue 8 (August 2016) - Khan, Mishal S; Osei-Kofi, Anna; Omar, Abbas; Kirkbride, Hilary; Kessel, Anthony; Abbara, Aula; Heymann, David; Zumla, Alimuddin; Dar, Osman
Summary: Involuntary migration is a crucially important global challenge from an economic, social, and public health perspective. The number of displaced people reached an unprecedented level in 2015, at a total of 60 million worldwide, with more than 1 million crossing into Europe in the past year alone. Migrants and refugees are often perceived to carry a higher load of infectious diseases, despite no systematic association. We propose three important contributions that the global health community can make to help address infectious disease risks and global health inequalities worldwide, with a particular focus on the refugee crisis in Europe. First, policy decisions should be based on a sound evidence base regarding health risks and burdens to health systems, rather than prejudice or unfounded fears. Second, for incoming refugees, we must focus on building inclusive, cost-effective health services to promote collective health security. Finally, alongside protracted conflicts, widening of health and socioeconomic inequalities between high-income and lower-income countries should be acknowledged as major drivers for the global refugee crisis, and fully considered in planning long-term solutions.